Characteristics Of Professional Teacher: A Psychological Review Of The Personality Of Prophet Muhammad Saw - Sutarto Sutarto; Dewi Purnama Sari (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2020)
This study aims to reflect on the Prophet Muhammad saw’s personality as a professional teacher from a psychological perspective to be understood and implemented by education personnel in carrying out their profession, both at school and outside of school. This research is library research, a study whose data comes from books, scientific journals, regulations, and research results. The analysis used is descriptive analysis with a reflective thinking approach. The results showed that Prophet Muhammad saw was a professional plus teacher because he had mastered and implemented three-plus competencies, namely personal religious competence, social religious competence, and spiritual pedagogical competence. This completeness is transcendental values. If these three plus professional competencies are owned, internalized, and implemented by the teacher, then the arrangement will change student behavior for the better.